The Role Of The Medical Committee Towards Services At Dr. H. Jusuf SK Tarakan Regional Public Hospital 2024 - Andi Irham Fasihi; Julia Fitrianingsih; Muhammad Idris Patarai (Jurnal EduHealth, 2024)
The role of the medical committee in health facilities includes several important sub-roles related to the credential committee, maintaining the quality of the medical profession, and maintaining the ethics of medical behavior. Each sub-role has certain challenges or problems that can affect the effectiveness of the committee in carrying out its duties. The purpose of this study was to analyze the influence of the role of the medical committee on services at the Dr. H. Jusuf SK Tarakan Regional General Hospital. The method in this study is a quantitative analytical survey, using a cross-sectional design. This study began with an initial survey to a research results seminar, starting from October 2024 until completion. The sample in this study was 89 people using the Accidental Sampling sampling technique. Data analysis in this study used the Chi-Square test. The results of this study indicate that out of 89 respondents, 51.7% had optimal doctor sub-credentials with a p value of 0.003 <0.05, optimal professional quality maintenance sub-value of 66.3% with a p value of 0.012 <0.05, good ethics and behavior sub-value of 57.3% with a p value of 0.005 <0.05. The results of the logistic regression test obtained the most dominant t value of the three independent variable indicators, namely the doctor sub-credentials with a partial t value of 2.436. Therefore, it is hoped that the head of the medical committee will provide more in-depth direction to the members of the medical committee regarding the implementation of credentials, maintaining the quality of the medical profession, maintaining professional ethics and behavior, in accordance with the Decree of the Minister of Health of the Republic of Indonesia.